Penumbuhan Lapisan Tipis µc-Si:H dengan Sistem Hot Wire PECVD untuk Aplikasi Divais Sel Surya - Syamsu Syamsu; Darsikin Darsikin; Iqbal Iqbal; Jusman Jusman; Toto Winata; Sukirno Sukirno; Mohamad Barmawi (Jurnal Matematika & Sains, 2005)
Microcrystalline hydrogenated silicon thin films have been grown on corning 7059 by using Hot Wire Plasma Enhanced Chemical Vapor Deposition (PECVD) system. Silane gas dilute in hydrogen gas (SiH4: H2 = 1 : 10 ) used as gas source. The effect substrate temperatures on deposition rate, optical, electrical and structural properties were analyzed. The deposition rate was varied from 3.22-5.24 µm/hour at temperature 175-275o C, SiH4 flow rate of 70 sccm, and filament temperature ~ 1000oC. The optical band gap varied from 1.13-1.44 eV at substrate temperature of 175-275. The Result XRD characterization of µc-Si: H thin film was grown at 275o C shows , , and orientation. Dark conductivities vary from 10-6-10-4 S/cm The Dark conductivity of µc-Si: H is higher than a-Si: H thin film. This result shows that µc-Si: H thin film is possible for p-i-n solar cells device application.